Hubungan pengetahuan dan sikap terhadap perilaku pencegahan komplikasi diabetes mellitus - Listina, Febria; Ghufronsyah, Muhammad Zakky; Rukmana, Nova Mega (Holistik Jurnal Kesehatan, 2025)
Background: Diabetes Mellitus (DM) is a non-communicable disease that can lead to serious complications if not properly managed. These complications include heart disease, kidney failure, vision impairment, and nerve damage. According to data from Comunity Health Center Way Halim II in Bandar Lampung, the number of DM cases increased significantly from 30 cases in 2020 to 472 cases in 2024. Furthermore, 141 cases were already recorded from January to April 14th, 2025 alone. Purpose: To determine the relationship between knowledge and attitudes toward complication prevention behavior among DM patients at Comunity Health Center. Method: A quantitative research used a cross-sectional design with 59 respondents selected by purposive sampling. Data were collected through structured questionnaires and analyzed using Chi-Square test. Results: The majority of respondents had poor knowledge and negative attitudes toward prevention. There was a significant correlation between knowledge (p=0.013; OR=3.2) and attitude (p=0.041; OR=2.7) with complication prevention behavior. Conclusion: Knowledge and attitudes play an important role in complication prevention behavior. Continuous health education and promotion are necessary to improve preventive practices among DM patients.   Keywords: Attitude; Complication Prevention; Diabetes Mellitus; Knowledge.   Pendahuluan: Diabetes Mellitus (DM) merupakan penyakit tidak menular yang dapat menimbulkan komplikasi serius seperti penyakit jantung, gagal ginjal, gangguan saraf, dan gangguan penglihatan. Kasus DM di Puskesmas Way Halim II meningkat dari 30 kasus pada 2020 menjadi 472 kasus pada 2024, dan pada awal 2025 tercatat 141 kasus. Tujuan: Untuk mengetahui hubungan pengetahuan dan sikap pasien terhadap perilaku pencegahan komplikasi. Metode: Penelitian kuantitatif dengan desain cross sectional pada 59 responden yang dipilih secara purposive sampling. Data dikumpulkan melalui kuesioner dan dianalisis dengan uji Chi-Square. Hasil: Sebagian besar responden memiliki pengetahuan kurang baik dan sikap negatif. Terdapat hubungan signifikan antara pengetahuan (p=0.013; OR=3.2) dan sikap (p=0.041; OR=2.7) dengan perilaku pencegahan komplikasi DM. Simpulan: Pengetahuan dan sikap berperan penting dalam perilaku pencegahan komplikasi. Edukasi dan promosi kesehatan berkelanjutan diperlukan untuk meningkatkan perilaku pencegahan pasien diabetes.   Kata Kunci: Diabetes Mellitus; Pengetahuan; Perilaku Pencegahan Komplikasi; Sikap.